Culture as a semiotic system: a redefinition of the idea of ​​culture from a systematic perspective - Pickel, Andreas (Cultura y Representaciones Sociales, 2018)
This paper incorporates a broad understanding of culture into Mario Bunge’s systemic philosophy. Cultures are viewed as semiotic systems. Semiotic systems are symbolic systems which include their users and view each culture as a semiotic system. This approach makes it possible to relate immaterial symbolic systems to real material social systems via semiotic systems, which are neither purely material nor purely ideal but combine elements of both. The goal is to sketch an ontology of culture that is consistent with emergentist materialism as well as being useful for the integration of culture into social science analysis.